2007
DOI: 10.1152/ajpheart.00874.2006
|View full text |Cite
|
Sign up to set email alerts
|

Very low-frequency blood pressure variability depends on voltage-gated L-type Ca2+channels in conscious rats

Abstract: Langager AM, Hammerberg BE, Rotella DL, Stauss HM. Very low-frequency blood pressure variability depends on voltage-gated L-type Ca 2ϩ channels in conscious rats. Am J Physiol Heart Circ Physiol 292: H1321-H1327, 2007. First published October 20, 2006; doi:10.1152/ajpheart.00874.2006.-The mechanisms generating highfrequency (HF) and low-frequency (LF) blood pressure variability (BPV) are reasonably well understood. However, little is known about the origin of very low-frequency (VLF) BPV. We tested the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 59 publications
(89 reference statements)
5
50
0
3
Order By: Relevance
“…The BP power at the heartbeat frequency was then calculated within a frequency range centered at the peak between 4 and 8 Hz with its edges defined by the points where the spectral density drops to 1% of the maximum power (27). These frequency bins were selected on the basis of our previous study (27) and their inclusion of various cardiovascular regulatory components (e.g., respiratory, Meyer waves, and myogenic activity) that have been suggested to contribute to BP oscillations (53,72).…”
Section: Animalsmentioning
confidence: 99%
“…The BP power at the heartbeat frequency was then calculated within a frequency range centered at the peak between 4 and 8 Hz with its edges defined by the points where the spectral density drops to 1% of the maximum power (27). These frequency bins were selected on the basis of our previous study (27) and their inclusion of various cardiovascular regulatory components (e.g., respiratory, Meyer waves, and myogenic activity) that have been suggested to contribute to BP oscillations (53,72).…”
Section: Animalsmentioning
confidence: 99%
“…In this context, it is well known that the endothelial-derived NO in rats modulates LF and VLF domains of blood pressure variability [28][29][30]. In fact, spectral analysis of the blood pressure recording suggests that the greater hypotensive response to nebivolol in tempol rats could be attributed to the NO pathway since nebivolol administration induced a reduction of VLF and LF only in the TN group.…”
Section: Discussionmentioning
confidence: 97%
“…Identification of the frequency components of blood pressure variability by power spectral analysis can potentially provide an approximation about mechanisms involved in blood pressure regulation [28][29][30]. In this context, it is well known that the endothelial-derived NO in rats modulates LF and VLF domains of blood pressure variability [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency components of blood pressure variability (BPV) detected by power spectral analysis include oscillations at the very low frequency (0.02-0.20 Hz in rats and 0.02-0.07 Hz in humans), low-frequency (0.2-0.6 Hz in rats and 0.077-0.15 Hz in humans), and high-frequency domain (1-4 Hz in rats and 0.15-0.40 Hz in humans) ( Table 2) [11]. In this context, while myogenic vascular function, renin angiotensin system, and endothelium-derived NO affect BPV at VLF [8,11], LF variability is modulated by sympathetic modulation of vascular tone and endothelial-derived NO in rats [11]. In addition, normalized LF (LF/HF ratio) has been validated as a marker of sympathetic vascular activity in preclinical and clinical studies [9,10].…”
Section: Ultra-short-term Blood Pressure Variabilitymentioning
confidence: 97%
“…Different mechanisms can contribute in the increase of beatto-beat BPV, including enhanced central sympathetic drive, reduced arterial or cardiopulmonary baroreflex, humoral and rheological factors, behavioral and emotional mechanisms, and changes in ventilation [13]. Beat-to-beat BPV has been used for the study of the mechanism of action of antihypertensive drugs and the diagnosis and treatment of patients with cardiovascular diseases [8,9,11]. For instance, in our laboratory, we have shown that carvedilol induced a greater hypotensive response in spontaneously hypertensive rats in comparison with normotensive control animals [14].…”
Section: Ultra-short-term Blood Pressure Variabilitymentioning
confidence: 99%